Analysis of the Carbon Emissions (Co2) Reduction in Waste Power Plants using Life Cycle Analysis - Khalifa Mansour Khalifa; Muhamad Haddin; Arief Marwanto (Universitas Islam Sultan Agung, 2022)
A Growth in energy demand Electricity in a city will show significant economic growth. Likewise, in the Libyan city of Sirte, economic growth per year is around 6% and with a population growth rate of around 2% per year, the city is struggling to get ahead. Thus, waste generated due to economic activities of the population also increased. While all the garbage is thrown away and not utilized. Separation of types of waste contributes to the economic potential for local governments to manage organized waste. In general, 37% of waste is disposed of in landfills, 8% of which are disposed of in organic form and put into sanitary machines that produce gas. While disposal to open areas around the world includes about 31% of waste with 19% recycled through composting and 11% burned at final disposal. The last recycled process, potentially has increased of CO emission in wasted power plant. To mitigate these situations, depth analysis of the procedure collection of the wasted power plant materials is proposed. In order to reduce carbon pollutant, life cycle analysis has been usage to measure the potential reduction of CO emission in Sirte City of Libya. The performance resuls shows that by using separation materials and life cycle analysis deployment has given significant contributions that able reducing CO emission of has reduced CO Emission. By supply of 1400 tons per day, it can be seen that the electricity production generated is 3.64 MJ which is 2.6% of the production generated from the total waste burned. With the resulting heat of 9.19 MJ, it is a total heat production of 3.7%. Of the emissions produced by the material, PVC contributed the largest contribution to pollution released from the incinerator by 57.7% compared to corrugated box / board which was only 15.2% and / or injection molding by 15.2%. By amounts of 1400 tons wasted assumption, the CO2 that can be generate based on LCA analysis is 2076.87 Kg, moreover, climate change index is equivalent to 3817.58 of CO2 (Kg). Ozon depletion has shown very wonderful grade as show -164.84, meaning that the release of CFCs into the air is significantly reduced. Low carbon index has been shown based on this results, LCA could perform best good treatment for wasted classification arranged with the LCA stage.